MlNERALOGICAL COMPOSITION AND PHYSICAL CHARACTERISTICS OF MUDDY FORMATIONS FROM THESSALONIKI AND CHALKIDIKI PREFECTURES - Καστρινάκη Α.; Τσιραμττίδης Α.; Μιχαηλίδης Κ.; Τρώντσιος Γ. (Bulletin of the Geological Society of Greece, 2004)
The myddy formations studied are characterized by the presence of abundant friable aggregates. Lithologically they belong to the sandy muds up to muddy sands. As their grain size decreases the percentage of the clay minerals increases significantly. Among the clay minerals illite predominates, while smectite, vermiculite, chlorite, kaolinite and their interstratified phases, follow. The presence of amphiboles and pyroxenes, as well as the high content of clay minerals and feldspars in these muddy formations, signify their mineralogical immaturity and the predominance of mild climatic conditions and thus mild weathering processes. The compaction and induration degree of the studied sediments is medium, because of the presence of grains of various granulometrie and mineralogical composition. Their swelling and shrinkage grade is relative high, because of the high content of smectite and its interstratified phases.